A “pithecoid feature” in skulls confirming possible neuro-psychiatric disorders. The diagnoses of an anthropologist of the nineteenth century - Ciliberti, Rosagemma; Siri, Anna; Iorio, Silvia; Lorettu, Liliana (Medicina Historica, 2020)
Background and aim: The interest for the morphological research of degenerative signs aimed at identifying personality pathologies characterized positive anthropology of the late nineteenth century. The increasing exploitation of statistical-epidemiological methodologies together with the recent neuroscientific acquisitions, risk dangerous effects on mono-factorial models on the understanding of antisocial behavior. Methods: Through historical analysis of the research carried out by the positivist anthropologist Giuffrida Ruggeri on the lack of the glenoid dimple of the temporal of the alienated, the authors examine the criticality of rigid and one-way psychopathological interpretative approaches also in relation to recent applications of neuroscience. Results: Increasingly, the scientific approach seems to abandon an interpretative vision anchored to rigid biological and statistical parameters to embrace a dimension adequate to the singularity and complexity of man. In this approach, neurosciences contribute to supporting the circularity of the interpretative model of antisocial behavior. Conclusion: Far from a deterministic return that assigns a decisive role to constitutional factors, new knowledge leads us to reflect on mutual, continuous and harbingers of biology and the environment in the characterization of the human being, in a constructive dialogue with ethics.